EFFECT OF ADVERTISED POLYHERBAL (AYURVEDIC) APHRODISIAC FORMULATIONS ON POTENT MALE ALBINO RATS - G KANASE, VANITA; KINI, RIDDHI; MANIYAR, DRASHTI; SHETTIGAR, SHRUTI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to study aphrodisiac activity of polyherbals on albino Wistar rats. Methods: Play Win and Ayurex are examples of the already marketed polyherbal formulations (PHFs), which are used in this study to determine their mating behavior and mating performance test activities in albino Wistar rats. Results: Both the test drugs Play Win and Ayurex created noteworthy increase in the mounting behavior of animals. It was also observed that mounting behavior activity (number of mounts) in Play Win, in the 1st h and the 3rd h, was greater than Ayurex. Administration of suspension of a single dose of Play Win, Ayurex, and sildenafil citrate concluded in the increase in the mating performance of the rats. The result of Play Win was found to be less than that of Ayurex and nearly the same as that of sildenafil citrate. Conclusion: From the research of the above-mentioned formulations with comparison to the standard drug (sildenafil), it is concluded that the PHFs are capable of producing aphrodisiac activity.